2013
DOI: 10.1590/s0034-71672013000700015
|View full text |Cite
|
Sign up to set email alerts
|

Produção de conhecimento em enfermagem: transposição e repercussões no ensino de graduação

Abstract: The research aimed to analyze the production of knowledge in nursing at a public university, in order to evaluate the impact of that production during the Nursing Graduation. An exploratory and descriptive research has been done in two stages. The first one consisted of gathering the reports of researches executed by the teachers who coordinated them from 2000 to 2009. As a result of this stage, it was mapped the type of studies performed, the themes and the theoretical and methodological references most utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…[3][4] On the other hand, studies have shown that there are few qualitative changes in health care practices, as well as scientific evidence that supports care as a complex and multidimensional system. [4][5] For Morin, one of the complex thinking authors, education necessarily goes through thought reform. According to the author's vision, it is necessary to replace thoughts that reduce and fragment with thoughts that distinguish, unite and integrate, meaning by complex, dynamic and evolutionary thinking.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4] On the other hand, studies have shown that there are few qualitative changes in health care practices, as well as scientific evidence that supports care as a complex and multidimensional system. [4][5] For Morin, one of the complex thinking authors, education necessarily goes through thought reform. According to the author's vision, it is necessary to replace thoughts that reduce and fragment with thoughts that distinguish, unite and integrate, meaning by complex, dynamic and evolutionary thinking.…”
Section: Introductionmentioning
confidence: 99%